The Lampropidae (Crustacea: Cumacea) of the World - Gerken, Sarah (Zootaxa, 2018)
Prior to the present study, the cumacean family Lampropidae included 114 species. This family is primarily found in temperate to cold waters. Revisions and investigation of museum collections yielded 12 new genera (Alamprops n. gen., Aplatysympus n. gen., Austrolamprops n. gen., Brachylamprops n. gen., Doieolamprops n. gen., Farragolamprops n. gen., Paraplatysympus n. gen., Phallolamprops n. gen., Phallolampropoides n. gen., Pseudoarchaeocuma n. gen., Quasiparalamprops n. gen., Reyssia n. gen.) and 23 new species (Aplatysympus neozealanicus n. sp., Austrolamprops sulcatus n. sp., Bathylamprops paraleucon n. sp., Brachylamprops scabridus n. sp., Chalarostylis bruunae n. sp., Doeiolamprops confundus n. sp., Farragolamprops seminalis n.sp., F. spinacristatus n. sp., Hemilamprops impellucidus n. sp., Lamprops northwindae n. sp., Misceolamprops concavus n. sp., Paraplatysympus aspericristatus n. sp., P. echinolowryi n. sp., Phallolamprops californiensis n. sp., P. pribilofensis n. sp., Phallolampropoides chukchiensis n. sp., Platytyphlops bamberi n. sp., P. echinatus n. sp., P. lowryi n. sp., P. petrescui n. sp., P. taylorae n. sp., Pseudoarchaeocuma bacescui n. sp., Quasiparalamprops chathamensis n. sp.). Additional description and Fig. of the ovigerous female and adult male of Watlingia chathamensis are provided. All new species and genera are described and illustrated, with diagnoses and keys to all genera and species. In addition, Mesolamprops bacescui is transferred to the Diastylidae as Diastylis bacescui (Gamô 1999).